Evaluación de la movilidad de elementos mayoritarios y trazas durante la milonitización de rocas del basamento de las Sierras Australes de Buenos Aires - Grecco, Laura Edith (2000)
Several authors have demonstrated thar the distribution of major and trace elements can be modified by processes such as meteorization or hydrothermal alteration. The mobility of chemical elements in ductile shear zones have been little studied, and the papers that deal with these problem are relatively recent.